Characterization and possible function of an enigmatic reflector in the eye of the shrimp Litopenaeus vannamei. (4th August 2020) - Schiffmann, Nathan; Wormser, Eyal Merary; Brumfeld, Vlad; Addadi, Yoseph; Pinkas, Iddo; Yallapragada, Venkata Jayasurya; Aflalo, Eliahu D.; Sagi, Amir; Palmer, Benjamin A.; Weiner, Steve; Addadi, Lia
Abstract : We characterize a reflector in the eye of the shrimp L. vannamei, which likely acts as a camouflage device to conceal the eye pigments in a largely transparent animal. Abstract : Reflective assemblies of high refractive index organic crystals are used to produce striking optical phenomena in organisms based on light reflection and scattering. In aquatic animals, organic crystal-based reflectors are used both for image-formation and to increase photon capture. Here we report the characterization of a poorly-documented reflector in the eye of the shrimp L. vannamei lying 150 μm below the retina, which we term the proximal reflective layer (PR-layer). The PR-layer is made from a dense but disordered array of polycrystalline isoxanthopterin nanoparticles, similar to those recently reported in the tapetum of the same animal. Each spherical nanoparticle is composed of numerous isoxanthopterin single crystal plates arranged in concentric lamellae around an aqueous core. The highly reflective plate faces of the crystals are all aligned tangentially to the particle surface with the optical axes projecting radially outwards, forming a birefringent spherulite which efficiently scatters light. The nanoparticle assemblies form a broadband reflective sheath around the screening pigments of the eye, resulting in pronounced eye-shine when the animal is viewed from a dorsal-posterior direction, rendering the eye pigments inconspicuous. We assess possible functions of the PR-layer and conclude that it likely functions as a camouflage device to conceal the dark eye pigments in an otherwise largely transparent animal.